Surgery for parapneumonic pleural empyema – What influence does the rising prevalence of multimorbidity and advanced age has on the current outcome?. Issue 2 (April 2016) - Schweigert, Michael; Solymosi, Norbert; Dubecz, Attila; Fernández, Marta Jiménez; Stadlhuber, Rudolf J.; Ofner, Dietmar; Stein, Hubert J.
Abstract: Objective: Pleural empyema is a critical condition. In the western world the share of sufferers with multiple comorbidities and advanced age is rapidly increasing. Methods: This retrospective study comprises all patients who underwent surgery for parapneumonic pleural empyema at a major center for thoracic surgery in Germany between January 2006 and April 2013. Results: A total of 335 patients (mean age 60.4 years) were included. The average ASA grade was 2.8. Empyema stage 1, 2 and 3 (classification of the American Thoracic Society) was encountered in 30, 230 and 75 cases, respectively. The most common comorbidities were cardiac disorders (124), diabetes mellitus (76), COPD (66) and alcoholism (54). The mean Charlson index of comorbidity score was 2. Minimally invasive surgery was feasible in 290 cases. A total of 88 patients sustained pulmonary sepsis. The overall mortality was 29/335 (8.7%). The occurrence of pulmonary sepsis (OR: 17.95; 95% CI: 6.38–62.69; p  < 0.001), respiratory failure (OR: 23.08; 95% CI: 8.52–73.35; p  < 0.001) and acute renal failure (OR: 8.20; 95% CI: 3.18–20.80; p  < 0.001) and Charlson score ≥ 3 (OR: 6.65; 95% CI: 2.76–17.33; p  < 0.001) were associated with higher mortality. On the other hand, very elderly sufferers (≥80 years) showed neither higher odds for pulmonary sepsis (OR: 0.78) nor for fatal outcome (OR: 0.92; 95% CI: 0.22–2.86; p  = 1). Conclusions: Parapneumonic pleural empyema is still associated with considerable morbidity and mortality. Pre-existing comorbidity, the occurrence of pulmonary sepsis and sepsis related complications have a determining influence on the results whereas advanced age itself shows no higher risk for adverse outcome. Further improvement seems achievable by earlier surgical intervention before the onset of pulmonary sepsis.